Regulation of GLUT4 expression in vivo and in vitro - Olson, Ann Louise; Knight, John B (Frontiers in bioscience, 2003)
The GLUT4 gene is subject to complex tissue-specific and metabolic regulation that has a profound impact on insulin-mediated glucose disposal. The regulation of this gene is of special clinical interest because insulin-mediated glucose homeostasis is highly sensitive to the levels of GLUT4 protein in muscle and adipose tissue. For this reason, the mechanisms of regulated expression of the GLUT4 gene have been intensively studied over the past decade. Understanding the transcriptional mechanisms that underlie the regulated expression of this highly differentiated gene have been slow to emerge, due to the paucity of suitable model systems available for detailed investigation. The development of transgenic mouse models to understand the mechanisms of transcriptional regulation has greatly enhanced our understanding of this gene. Information gained about the regulation of the GLUT4 gene has provided insight into mechanisms by which complex gene regulation occurs through a small number of cis-acting regulatory elements.